Be cool to be far: Exploiting hibernation for space exploration. (September 2021) - Cerri, Matteo; Hitrec, Timna; Luppi, Marco; Amici, Roberto
Highlights: Torpor/hibernation is a state characterized, in mammals, by a drastic reduction of metabolic rate. Torpor induces physiological changes that could counteract the side effects of a prolonged stay in space. A state mimicking torpor, called synthetic torpor, can be induced in non-hibernators by acting of the neural control of metabolism. To enhance the potential of torpor-derived technology for space application, it is necessary to move from Earth-based studies to the International Space Station. Synthetic torpor may open new scenario for the human exploration of the solar system and be a safe method to ship animals to future space colonies. Abstract: In mammals, torpor/hibernation is a state that is characterized by an active reduction in metabolic rate followed by a progressive decrease in body temperature. Torpor was successfully mimicked in non-hibernators by inhibiting the activity of neurons within the brainstem region of the Raphe Pallidus, or by activating the adenosine A1 receptors in the brain. This state, called synthetic torpor, may be exploited for many medical applications, and for space exploration, providing many benefits for biological adaptation to the space environment, among which an enhanced protection from cosmic rays. As regards the use of synthetic torpor in space, to fully evaluate the degree of physiological advantage provided by this state, it is strongly advisable to move from Earth-based experiments to 'in the field' tests, possibly on board the International Space Station.